Leukaemia survival trends in children with Down's syndrome in Great Britain, 1971–2000: a population-based study. Issue 7 (24th August 2009) - Shah, Anjali; Stiller, Charles; Lancaster, Donna; Vincent, Tim; Coleman, Michel P
Abstract : Background: Children with Down's syndrome (DS) who developed leukaemia have had a worse prognosis than other children with leukaemia in the past. In the 1970s and early 1980s, some children with DS who developed leukaemia received fewer cycles of chemotherapy or were advised not to have treatment. Methods: In this population-based study, trends in 5-year survival from leukaemia were evaluated for children with and without DS who were diagnosed in Great Britain during 1971–2000 and followed to the end of 2004. Results: For all children, with and without DS, survival has increased dramatically over the 30 year study period. For lymphoid leukaemia, survival in children with DS increased, but remains lower than for other children (5-year survival 59% vs 83% during 1996–2000). For acute non-lymphoblastic leukaemia (ANLL), however, 5-year survival improved substantially for children with DS, from less than 1% in the early 1970s to over 80% in the 1990s. For other children, survival increased from 6% to 64% during the same period. Conclusion: Survival for all children diagnosed with leukaemia has improved during the last three decades. For lymphoid leukaemia, the inferior outcome observed on more recent treatment protocols in children with DS remains an area for concern. For ANLL, the improvement in survival for children with DS is due to a number of factors, namely increased recruitment of these children to clinical trials, changes in clinical practice and important differences in the biology of myeloid leukaemia in young children with DS, resulting in a better response to some chemotherapeutic agents.